1980
DOI: 10.1039/dt9800000090
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic carbenemetal complexes. Part 1. Cationic chromium(I) complexes and the chemistry of their chromium(0) precursors and of related molybdenum(0) and Tungsten(0) complexes, especially with bulky carbene ligands C(OR′)R[R  CH(SiMe3)2or CH2SiMe3]

Abstract: Die Carbenmetall(0)‐Komplexe (II) werden ausgehend von den Hexacarbonylen (I) durch sukzessive Umsetzung mit entsprechenden Organyl‐Li‐ Verbindungen und Alkylierungsreagenzien dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The very similar ESR spectrum was also observed in the oxidation of 1 (g = 2.005, A N = 5.0 G, A H = 1.3 G) with (4-BrC 6 H 4 ) 3 -NSbCl 6 . In contrast, in LappertÕs imidazolylnylidene chromium radical cation complexes [5], these radicals are not coupled with nitrogen but coupled with only Cr and coordinated phosphines (Fig. 4).…”
Section: Oxidation Of the Chromium Complexesmentioning
confidence: 79%
See 2 more Smart Citations
“…The very similar ESR spectrum was also observed in the oxidation of 1 (g = 2.005, A N = 5.0 G, A H = 1.3 G) with (4-BrC 6 H 4 ) 3 -NSbCl 6 . In contrast, in LappertÕs imidazolylnylidene chromium radical cation complexes [5], these radicals are not coupled with nitrogen but coupled with only Cr and coordinated phosphines (Fig. 4).…”
Section: Oxidation Of the Chromium Complexesmentioning
confidence: 79%
“…To clarify the oxidized state, the benzimidazolylidene ligand was chosen partly because the radical cation species might be stabilized by delocalization through the enlarged p-conjugation. In this paper, we describe a general route to a series of (benzimidazolylidene)Cr(CO) 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1980, Lappert et al [58] reported that cationic Cr(I)-NHC complexes Cr-58(a-c) (Figure 4.6) could be prepared through the oxidation of their Cr(0) precursors Cr-4(a,b) and Cr-3 with …”
Section: Cr(i)-nhc Complexesmentioning
confidence: 98%
“…A series of Group 6 M(0) carbonyl complexes Cr-1(a,b), Mo-1(a-c), W-1(a,b), Mo-2(a,b), Mo-3a, Mo-4, and Cr-2 have been prepared through cleavage of electron-rich olefins with metal carbonyl precursors under thermal conditions [Cr-1a, M = Cr, n = 1, R = Me Cr-1b, M = Cr, n = 1, R = Et Mo-1a, M = Mo, n = 1, R = Me Mo-1b, M = Mo, n = 1, R = Et Mo-1c, M = Mo, n = 1, R = Bz Mo-3a, M = Mo, n = 2, R = Me W-1a, M = W, n = 1, R = Me W-1b, M = W, n = 1, R = Et Mo-2a, n = 1, R = Me Mo-2b, n = 1, R = p-Tol Mo-4, -4a, M = Cr, R = Et, L^L = dmpe Cr-4b, M = Cr, R = Et, L^L = dppe W-4a, M = W, R = Et, L = dppe W-4b, M = W, R = Bz, Reactivity of Cr-1(a,b), Mo-1(a-c), and W-1(a,b)towards phosphine and pyridine[55][56][57][58] 2.1.1.1 Cyclisation route In 1986, Fehlhammer et al reported that hydrogen isocyanide complexes M(CO) 5 (CNH) (M = Cr, Mo, W) reacted with aziridines at r.t. through protonation of aziridine, nucleophilic attack of cyano-N atom and ring-opening followed by intramolecular cyclisation, to give the imidazolidin-2-ylidene complexes Cr-1(c-e), Mo-1d and W-1c. Complex Cr-1f can be obtained when Cr(CO) 5 (CNH) reacting with N-methylaziridine but at higher temperature (60 °C).…”
mentioning
confidence: 99%